Digital Transformation Challenges: Adaptation Of Filing Systems by Civil Servants In Mataram City - Mustamin H. Idris; Asfarony Hendra Nazwin; Anindia Rizkila Cahyani; Reza Apriani; Indah Sari (Journal of Public Administration and Government, 2024)
Digital transformation is a government effort towards effective and efficient public service delivery. To expedite services and adapt to evolving technology, government agencies are required to adapt to the developments. This research aims to understand the biggest challenges and adaptive efforts of the Mataram City government in facing digital transformation in the context of archival management or the implementation of SRIKANDI as an effort to enhance the quality of public services. This study employs a qualitative method with a descriptive approach. Data collection techniques include direct observation, interviews, and documentation. The findings indicate that Mataram City faces challenges in digital archival transformation both before and during the implementation of SRIKANDI. The major constraints include human resource skills. Adaptive strategies are focused on improving human resource quality through intensive training, direct mentoring, and periodic evaluation. Effective collaboration among archivists, stakeholders, and technical teams is considered key to the success of digital transformation. Thus, this research contributes to understanding the challenges and solutions in digital archival transformation within local government settings.